A farewell to class: the Japanese new left, the colonial landscape of Kamagasaki, and the Anti-Japanese front (1970-75) - Knaudt, Till (Journal of Japanese studies, 2020)
With the end of the Japanese student movement in 1970, activists of the militant New Left sought a new revolutionary subject. Turning their attention toward Japan's minorities, activists discovered the day laborers in the "inner colony" of Osaka's Kamagasaki district. Calling for revolution by the lumpenproletariat, the activists now understood the salaried working majority as colonial oppressors. As manifestation of this political shift, the Anti-Japanese Front of 1974 practiced terrorism, bombing several companies, injuring and killing white-collar workers. This article shows how the violence by anti-Japanese activists was entangled in anti-imperialist theory, social movement praxis, and the shift away from class politics. (J Jpn Stud/GIGA)